The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1120/jacmp.v17i5.6041
|View full text |Cite
|
Sign up to set email alerts
|

Surface imaging, laser positioning or volumetric imaging for breast cancer with nodal involvement treated by helical TomoTherapy

Abstract: A surface imaging system, Catalyst (C‐Rad), was compared with laser‐based positioning and daily mega voltage computed tomography (MVCT) setup for breast patients with nodal involvement treated by helical TomoTherapy. Catalyst‐based positioning performed better than laser‐based positioning. The respective modalities resulted in a standard deviation (SD), 68% confidence interval (CI) of positioning of left–right, craniocaudal, anterior–posterior, roll: 2.4 mm, 2.7 mm, 2.4 mm, 0.9° for Catalyst positioning, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 26 publications
0
42
2
2
Order By: Relevance
“…Crop et al . 19 studied the setup error based on laser light, Catalyst and mega voltage computed tomography (MVCT) in postoperative radiotherapy for breast cancer. The results showed that the setup error of the Catalyst was significantly better than that of laser-based positioning and was very close to the MVCT.…”
Section: Discussionmentioning
confidence: 99%
“…Crop et al . 19 studied the setup error based on laser light, Catalyst and mega voltage computed tomography (MVCT) in postoperative radiotherapy for breast cancer. The results showed that the setup error of the Catalyst was significantly better than that of laser-based positioning and was very close to the MVCT.…”
Section: Discussionmentioning
confidence: 99%
“…This OSS system is unique because it uses a deformable algorithm to calculate the isocenter position. The principle behind the deformable registration in depth scans is described by Hao Li et al Recently published results showed that patient setup using the deformable algorithm of the Catalyst TM system was superior to LBS for breasts with nodal involvement in TomoTherapy (Accuray, Sunnyvale, CA) . The work carried out by Crop et al used mass‐weighted PTV location for patient setup, specially designed for the TomoTherapy environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that SGRT cannot replace internal imaging for SBRT, but quantifying the effects of adding SGRT to the traditional IGRT chain for SBRT (referred to as SG‐SBRT for the remainder of the text) can help elucidate the benefits of this technology. There is literature describing the benefits of utilizing SGRT for deep inspiration breath‐hold treatments of left‐sided breast cancer patients, other breast cancer treatments, and stereotactic radiosurgery, but limited publications on its use for other sites or for initial positioning of SBRT patients . The aim of this retrospective study is to establish the utility of optical surface imaging for initial patient setup in SBRT treatments and to formulate a proposed initial positioning process by studying the impact of orthogonal kV imaging when SG‐SBRT is used and the effects of reference surface type selection (from treatment planning CT versus camera‐acquired in the room) on its performance.…”
Section: Introductionmentioning
confidence: 99%